REVIEW OF STATE FINANCIAL DAMAGES IN LAWS TO THE NAME OF THE NABABAN HOTASI - NADYA DEFANI RIESTIRA SCHOUTEN (Sekolah Tinggi Ilmu Hukum Awang Long, 2020)
This study analyzes Law Number 19 of 2003 concerning State-Owned Enterprises ( BUMN ), Law Number 17 of 2003 concerning State Finance and Law Number 20 of 2001 in conjunction with Law Number 31 of 1999 concerning Eradication of Corruption in relation to the definition of regarding state finances. The problem that then arises is when there is a difference in the definition of state finances regulated in the law, so that when the Directors of SOEs ( BUMN ) issue policies that result in losses, then law enforcement officials are charged with Article 2 and Article 3 of Law Number 20 of 2001 Concerning Eradication of Corruption.